f(x)=-12x+48

Simple and best practice solution for f(x)=-12x+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=-12x+48 equation:


Simplifying
f(x) = -12x + 48

Multiply f * x
fx = -12x + 48

Reorder the terms:
fx = 48 + -12x

Solving
fx = 48 + -12x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.
f = 48x-1 + -12

Simplifying
f = 48x-1 + -12

Reorder the terms:
f = -12 + 48x-1

See similar equations:

| .3x-2.3=.1 | | 2(4y-3)=-10 | | -7w+2(w+4)=3 | | 8+x=-21 | | -32+t+18= | | 5y+12=57 | | 12=x^2-4 | | 10x+y=7(x+y) | | -25+2v=-56v-42 | | 50c+5f+10cr+fr=0 | | r^2-r+2=7 | | X+5+3x+5=180 | | y+3=-.5(x+5) | | 7b=6b-9 | | -5(2t-2)+6t=5t-6 | | (-19)+x=-33 | | 40=2y+12 | | 0.04(y-7)+0.12y=0.20y-.6 | | 36x^3-15x=0 | | Ax+5=bs-c | | k-4-6=-16 | | 3y-1=x+5 | | 3x^6+6x^4-24x^5=0 | | 5(2x-1)+4x+2=11 | | x-126=35+8x | | -4=x+-7 | | Y=-16x^2+16x+5 | | Ax+5=bc-c | | x=9x+5-5 | | 6n+4=-2n | | (-32)+x=-18 | | 48kd=3.2k |

Equations solver categories